Sizing and designing of an adsorption chiller with phase change material thermal storage for an office building: Case study Nigeria - Mkpamdi Eke; Tagne Takote Brice Clausel; Cosmas Anyanwu; Onyekwere Ojike; Fidelis Abam (Next Energy)
Nigeria receives an average of 6.29 kW/m²/day of solar radiation, making it ideal for solar-assisted cooling systems. In this study, a feasibility study of integrating solar-driven adsorption chiller was conducted for a 24 m³ office at the University of Nigeria, Nsukka using a silica gel-water pair. The prototype features a double-stage, 2-bed heat and mass recovery design with thermal energy storage as innovation to cover the mismatch between the day and night as well as during distrust time of solar collector. Results showed a cooling load of 2.7–3.5 kW, requiring a cooling capacity of 250 W/m² over 10 h with a performance coefficient (COP) of 0.68. A solar power input of 3.5–7.5 kW was achieved with an evacuated tube collector area of 1.75 m². The study validated the use of 28 kg of paraffin wax for heat storage and demonstrated a refrigeration capacity of 9406 kJ and cooling effect of 715.43 kJ with a cycle performance’s coefficient COPcy of 0.08 as well as specific cooling power (SCP) of 77 W/kg. This model offers a promising solution for sustainable cooling in Nigeria's climate especially and in Africa globally. However, the developed model can generate up to 8 kW cooling power with 23 kg of silica gel, which slightly exceeds the typical office size. This is characterized by the smallest office parameters that may affect the system’s performance due to the weather conditions. Thus, some parameters considered are slightly scaled up enabling the integration of more than one office.